The depigmenting effect of natural resorcinol type polyphenols Kuwanon O and Sanggenon T from the roots of morus australis. (4th January 2017) - Hu, Shuting; Zheng, Zongping; Chen, Feng; Wang, Mingfu
Abstract: Ethnopharmacological relevance: Morus australis, one of the major Morus species growing in East Asia, is rich in phenolic compounds. The extract of M. australis has been used as skin whitening components for a long period. The action mechanisms of its principal constituents are still unclear. This study aims to evaluate the skin lightening effects of phenolic compounds extracted from the root of M. australis in different melanocyte systems and artificial skin models. Materials and methods: The depigmenting effect of resorcinol type polyphenols (RTPs) from the root extract of M. australis was evaluated in murine b16 and melan-a cell lines using a combined sulforhodamine B assay. Tyrosinase activity and the expression of melanogenesis proteins were evaluated for the mechanism study. The artificial skin model is used as a replacement of the animal test. Results: Only Kuwanon O and Sanggenon T were found to have significant depigmenting effects in both murine b16 and melan-a cell lines. Their depigmenting mechanisms are slightly different in the two cell systems. In b16 cells, Kuwanon O and Sanggenon T, together with the other two RTPs, induced post-transcriptional degradations of MITF without suppressing its mRNA expression, leading to significant decreases of TRP-1 and TRP-2 production. While in melan-a cells, the levels of tyrosinase families were suppressed via MITF downregulation at both transcription and translation level by RTPs, with Kuwanon O inducing the greatest suppression. Further evaluations in artificial skin model demonstrated the outstanding depigmenting effects of Kuwanon O and Sanggenon T. Conclusions: Kuwanon O and Sanggenon T from M.australis root extract are two potential skin whitening ingredients. To screen resorcinol flavonone derivatives with an isoprenyl group in the Diels-Alder substituent might be an option for the search of potent hypopigmenting agents from plants. Graphical abstract: